2021
DOI: 10.3389/fimmu.2021.684727
|View full text |Cite
|
Sign up to set email alerts
|

The Ability of AhR Ligands to Attenuate Delayed Type Hypersensitivity Reaction Is Associated With Alterations in the Gut Microbiota

Abstract: Aryl hydrocarbon receptor (AhR) is a ligand-activated transcription factor that regulates T cell function. The aim of this study was to investigate the effects of AhR ligands, 2,3,7,8-Tetrachlorodibenzo-p-dioxin (TCDD), and 6-Formylindolo[3,2-b]carbazole (FICZ), on gut-associated microbiota and T cell responses during delayed-type hypersensitivity (DTH) reaction induced by methylated bovine serum albumin (mBSA) in a mouse model. Mice with DTH showed significant changes in gut microbiota including an increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 71 publications
0
22
0
Order By: Relevance
“…Lymph nodes are considered the site of immune response initiation against pathogens [ 82 ]. Previous studies from our lab have demonstrated the role of MLNs in the modulation of microbiomes [ 35 ]. Another important study has shown that mesenteric lymph nodes significantly attenuated inflammatory biomarkers of the lung to preserve barriers in a septic model of rats [ 83 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lymph nodes are considered the site of immune response initiation against pathogens [ 82 ]. Previous studies from our lab have demonstrated the role of MLNs in the modulation of microbiomes [ 35 ]. Another important study has shown that mesenteric lymph nodes significantly attenuated inflammatory biomarkers of the lung to preserve barriers in a septic model of rats [ 83 ].…”
Section: Discussionmentioning
confidence: 99%
“…The MLN cells were stained using fluorescent conjugated antibodies (anti-CD3 Brilliant Violet 785, anti-CD4 Phycoerythrin (PE), anti-CD8 Alexa Fluor 700, anti-Vβ8 FITC (Fluorescein isothiocyanate), and anti-NK1.1-PE/Dazzle. The staining of cells for dual markers was performed as described previously [ 35 ]. In brief, Fc receptor block was added to the MLN cells which were incubated for 10 min at room temperature, followed by staining of the cells using appropriate antibodies then incubation at 4 °C for 20–30 min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interaction between gut microbiota and the host is important for maintaining immune homeostasis (Chu and Mazmanian, 2013). Gut bacteria have been shown to influence the polarization of lymphocyte subpopulations and their cytokines and thereby regulate immune functions (Abdulla et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the exogenous ligands (2,3,7,8-tetrachlo-rodibenzo-p-dioxin (TCDD), benzo[a]pyrene, β-naphthoflavone, etc. ), that have been examined extensively [ 51 , 52 , 53 , 54 ], many other endogenous and dietary AhR ligands have been identified and show differential properties upon ligand activation [ 55 , 56 ].…”
Section: Introduction To Ahrmentioning
confidence: 99%